Animal welfare and biosecurity correlation in buffalo farm evaluated by ClassyFarm system - Domenico Vecchio (Revista Científica, 2023)
ClassyFarm is an integrated system for categorizing farms according to the risk assessment (RA) methodology. It is an Italian innovation aimed at improving the synergy between breeders and competent authorities to improve the safety and quality of food of animal origin. ClassyFarm gathers and processes data referred to in the following areas: biosecurity, animal welfare, health, and antimicrobial usage. It can be applied to livestock species, including water buffaloes. Upon request of the Italian Ministry of Health (IMH), the National Reference Centre on Water Buffalo Farming and Production Hygiene and Technologies (CreNbuf), in collaboration with the Italian Reference Centre for Animal Welfare (CreNBA), developed a RA-based checklist (CL) for the on-farm assessment of buffalo welfare and farm biosecurity level, included in the ClassyFarm system. The multiple- choice CL consists of 79 items. Each item is scored according to 3 categories: “insufficient”, “acceptable” and “excellent”. The assessment system for animal welfare includes non-animal-based (N-ABMs) and animal-based measures (ABMs). N-ABMs are divided into two macro-areas: Area A (32 items): “Management factors” and Area B (31 items): “Housing factors”. ABMs are assessed in Area C (17 items). Biosecurity was assessed using 15 indicators. The CL has been tested in 102 farms, with an average size of 412 heads. On average, the overall welfare value was 61.55% (on a scale from 0 to 100%), and the average biosecurity score was 43.31%. The statistical analysis was performed by Spearman Rank correlation coefficient using GraphPad Prism 8.0.1. (GraphPad Software, San Diego, CA, USA). The two variables were positively correlated (Spearman’s Rho=0.501; p<0.001). The average welfare values of the specific areas were: A, 61.76%; B, 42.17%; C, 70.43%. At least one potential legislative non-compliance was recorded in 39.80% of the farms. The highest correlations between the different areas of well-being and biose-curity are found for the management areas, highlighting how management is essential to ensure both the levels of well-being and those of biosecurity. These CLs represent a functional and effective tool to assign animal welfare and biosecurity indexes to farms, improving farm management and housing conditions, giving answers to consumers, and adding value to farmers’ good practices. The IMH is promoting the application of this system at European and international levels.